Anxiety and Depression Symptoms among Quarantined Adults and Related Risk Factors During COVID-19 Pandemic: A Cross-Sectional Study - Khalid Alsaadi; Khalid Algaali; Eman Elsayed Abd-Ellatif; Sami Almudarra; Ali Almoqbali; Fatima Al Hashmi; Vidyanand Vaidya; Salah T. Al Awaidy (Dr. Sulaiman Al Habib Medical Journal)
Background: Quarantine, characterized as isolation, may either initiate or intensify mental health disorders such as anxiety or depression. Researchers have assessed the risk variables related to these diseases during the coronavirus (COVID-19) pandemic. We assessed the prevalence of anxiety and depression, in addition to identifying related risk variables, among confined Omani adult citizens in northern Oman. Methods: We performed cross-sectional research among citizens of ages 18 and higher who were quarantined for a minimum of 10 days owing to travel or contact with infected persons. We used convenience sampling, with respondents self-reporting sociodemographic information, chronic illnesses, quarantine status, lifestyle choices, COVID-19 infection status, and symptoms of anxiety and depression by using an electronic questionnaire disseminated through WhatsApp. We evaluated anxiety and depression symptoms by using the Hospital Anxiety and Depression Scale. Results: Out of 567 participants, 46% experienced heightened anxiety symptoms, whereas 67% reported elevated depressive symptoms. In the 26–45-year age group, higher proportions of anxiety (85%, P value 0.98, CI 0.64–1.59) and depression (83%, P value 0.22, CI 0.46–1.20) were observed. Among the female respondents, 74% indicated experiencing anxiety (P value 0.003, CI 1.16–1.98) and 66% reported depressive symptoms (P value 0.009, CI 0.51–0.91), while 26% of male respondents reported anxiety and 34% reported depressive symptoms. Among the married respondents, 82% reported experiencing feelings of anxiety (P value 0.057, CI 0.99–2.20) and depression (P value 0.07, CI 0.98–2.21). Among the respondents with confirmed COVID-19, 52% reported symptoms of anxiety (P value 0.33, CI 0.64–1.16) and depression (P value 0.002, CI 1.18–2.09). Among the respondents quarantined for 10–14 days, 58% reported anxiety (P value 0.026, CI 1.04–1.90) and depressive symptoms (P value 0.39, CI 0.85–1.54). Conclusions: Our findings underscore the significant psychological vulnerabilities among individuals quarantined during the COVID-19 pandemic. It is important to address the mental health support needs of such groups by providing services such as psychiatric hotlines.